2007
DOI: 10.1007/s00264-006-0271-z
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary fixation of tibial shaft fractures: a comparison of the unlocked and interlocked nail

Abstract: The study is a prospective evaluation and comparison. Eighty-two patients with tibial shaft fractures were treated with intramedullary fixation by either an unlocked nail (ULN) or an interlocked nail (ILN). All patients were followed up for 12 months with a functional score evaluation. The patients were divided into two groups, based on the method of treatment. The ULN group included 42 patients with an average age of 43.1 years. The ILN group included 40 patients with an average age of 40.0 years. Both groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
0
11
0
6
Order By: Relevance
“…In their study, the mean time until union was 16.2 weeks in unlocked IM nailing group. [10] In our study, the mean time until union was four weeks longer in talon tibial IM nailing group when compared to conventional distal locked tibial IM nailing group. However, time until union was slightly similar to the results reported in the literature.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In their study, the mean time until union was 16.2 weeks in unlocked IM nailing group. [10] In our study, the mean time until union was four weeks longer in talon tibial IM nailing group when compared to conventional distal locked tibial IM nailing group. However, time until union was slightly similar to the results reported in the literature.…”
Section: Discussionmentioning
confidence: 70%
“…[8] Ghafil et al [9] reported the results of expandable tibial IM nailing in 52 patients with OTA 42A and 42B fractures; in this study, the mean time until union was 15.8 weeks. On the other hand, Lee et al [10] compared unlocked tibial IM nailing with locked tibial nailing and found no significant difference in healing time and malunion rate. In their study, the mean time until union was 16.2 weeks in unlocked IM nailing group.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, intramedullary nail fixation has been shown to be an effective method for treating both open and closed tibial fractures [6][7][8]. However, the choice between two alternative intramedullary nailing approaches, reamed or unreamed, is an ongoing controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Lee ve ark., [7] tibia cisim kırıklarında, kilitli ve kilitsiz kanal içi çivilemeleri karşılaştırdıkları çalışma-larında; fonksiyonel skor, kaynama oranları, iyileşme zamanı ve kötü kaynama açısından önemli bir fark bulmamakla beraber ameliyat süresi ve insizyonun uzunluğu açısından kilitsiz grubun avantajlı olduğunu ancak işe dönme süresinin kilitli çivilemede anlamlı şekilde daha kısa olduğunu belirtmişler, kilitsiz kanal içi çivilemenin tibia cisim kırıklarında basit ve etkili bir yöntem olduğunu bildirmişlerdir.…”
Section: Discussionunclassified
“…[2,5] Diğer yandan, kilitsiz kanal içi çivileme, uygulama kolaylığı, kısa cerrahi süresi, daha düşük radyasyona maruz kalma gibi avantajlara sahipken özellikle rotasyonel instabilite, çivinin proksimale yer değiştirmesi, kötü kaynama (malunion) ve bazen alçı gibi ek tespit gerektirmesi bu yöntemin dezavantajları-nı oluşturmaktadır. [6,7] Bu retrospektif çalışmada, kilitli ve kilitsiz kanal içi çivileme ile tedavi edilen tibia cisim kırıklarının fonksiyonel ve radyolojik sonuçlarının karşılaştırılması amaçlandı. rekurvasyon, rotasyon, kısalık), komşu eklemlerde hareket, ağrı, yürüme ve ağır aktiviteler değerlendirildi.…”
unclassified